Use of cutting guides during craniosynostosis sequelae surgery: A comparative study between computer-assisted planning and post-operative results. Issue 7 (July 2017) - Queiros, Chrystelle; Joly, Aline; Paré, Arnaud; Listrat, Antoine; Travers, Nadine; Goga, Dominique; Laure, Boris
Abstract: Background: The authors compared results of craniofacial reconstruction surgery using cutting guides with planned reconstruction on patients presenting craniosynostosis surgery sequelae. Methods: This is a retrospective study performed on seven patients who had undergone craniofacial reconstructive surgery in University Hospital Center of Tours (France) in 2015. Patients had long-term sequelae of trigonocephaly and anterior plagiocephaly surgery. 3D computer model was constructed, based on CT scans and used for surgical planning. Cutting guides were realized to use patient autologous bone. Post-operative 3D cranioplasty was superimposed to the 3D pre-operative to determine the minimal distance between each point of the post-operative flap and its pre-operative point corresponding. Results: Mean of minimal distances calculated per patient ranged from 0.89 mm to 1.85 mm. The best result for percentage of points having the minimal distance inferior to 1.8 mm was 98.2 percent; the worst result was 55 percent. This value ranged from 77.5 to 98.2 percent for trigonocephaly cases. This value ranged from 55 to 77.5 percent for plagiocephaly cases. No significant difference was found between pre and post-operative areas and volumes of each flap, p = 0.12 and p = 0.19 respectively. Conclusion: Using cutting guides facilitates complex craniofacia reconstructions with patient autologous bone and obtains precise and reproducible results.